Grodkow as a center of the judiciary - Menzel, Mateusz (The Opole Studies in Administration and Law, 2019)
The article refers to the history of the judiciary in the town and the county (poviat) of Grodków which is presently located in Opolskie Voivodeship. In the first chapter, a short history of the establishment of the town, description of its owners, the process of creation of the administrative structure and some titbits of the town’s history are presented. In the consecutive parts, the history of the foundation and activity of several courts which operated in the town is presented. An analysis of the files concerning the town and court records preserved in the State Archives in Opole is also made. In the last but one chapter, a list of first people representing a new judiciary system in postwar Poland in the territory of the voivodeship and the poviat is presented. The article ends with a description of the last court operating in the town, that is the county court.